Implementasi Sistem Pengamanan Lingkungan Terpadu Berbasis Desa Adat di Wilayah Hukum Kepolisian Sektor Kuta Utara - I Made Arjaya; I Wayan Wesna Astara; Ni Putu Diah Kurniawandari (Postgraduated Community Service Journal, 2022)
In the case of non-petty crimes, you must cooperate with local residents and the police, as Bali itself adheres to a traditional village system, with guard badges and a nationally recognized special security system. on legal basis. namely Bali Governor Regulation Number 26 of 2020 concerning the Integrated Village-Based Environmental Protection System (Sipandu Adat). The intent of this provision is very good, but its implementation will not be possible without obstacles and shortcomings. Based on this background, the formulation of the problem was found, namely How is the Legal Arrangement of the Traditional Village-Based Integrated Environmental Security System in terms of the Bali Governor Regulation Number 26 of 2020 concerning the Traditional Village-Based Integrated Environmental Security System in the Police Legal Area of the North Kuta Sector, and How are the implementation and obstacles in implementation of the Governor of Bali Regulation Number 26 of 2020 concerning the Integrated Village-Based Environmental Security System in the North Kuta Sector Police Legal Area. Research on the Implementation of Bali Governor's Regulation Number 26 of 2020 concerning an Integrated Environmental Security System Based on Traditional Villages by the North Kuta Sector Police is an empirical legal research with a sociological juridical type based on normative legal science. The conclusion of this study is that the Legal Regulation of the Integrated Village-Based Environmental Protection System already has a clear legal umbrella, which has been regulated in Bali Governor Regulation number 26 of 2020 regarding integrated environmental security based on traditional villages. Then the obstacle in implementing the Bali Governor Regulation Number 20 of 2020 is related to the lack of funding.